PELAKSANAAN MANAJEMEN PROGRAM VAKSINASI COVID-19: ANALISIS DUKUNGAN MAHASISWA : Covid-19 Vaccination Program Management Implementation: College Student Support Analysis - Donny Yunamawan; Puji Astuty (Forind Press, 2024)
Along with the ongoing improvement in the current condition of Covid-19 in Indonesia, there has been an increase in community mobility, especially for students who are currently starting to be active again in lecture activities. Therefore, it is important to take care of yourself and the surrounding environment as an effort to prevent the transmission of Covid-19 to maintain conditions that are currently getting better. This study aims to analyze the precede proceed model in the behavior of preventing the transmission of Covid-19 in students. The method in this study used a quantitative method with a cross-sectional design. This research involved 200 respondents which were conducted in April-June. The sampling technique used in this research is probability sampling using a simple random sampling method. Collecting data using a questionnaire distributed online using google forms. The analysis technique in this study uses multiple linear regression test. The results showed that attitudes (b = 0.22, 95% CI = 0.06 - 0.38, p = 0.008), infrastructure (b = 0.48, 95% CI = 0.05-0.92, p = 0.029), and support from friends (b = 0.60 , 95% CI = 0.18-1.03, p = 0.006) is a factor that influences the behavior of preventing the transmission of Covid-19.